Precollege Risk Markers for College Rape and Verbal Sexual Coercion: Same or Different? - Sell, Nichole M. (Journal of interpersonal violence, 2024)
Verbal sexual coercion (VSC) and rape are common experiences among college women. Although they have been theorized to involve different risk markers, few prospective studies have examined predictors of VSC and rape separately. The present prospective study was designed to identify precollege risk markers for VSC and rape in first-year college women, with the goal of considering the degree to which they overlap or differ. Women (N = 449) recruited from the community just prior to high school graduation completed measures of sexual victimization (SV) since age 14 but prior to college, sexual refusal assertiveness, high school heavy episodic drinking (HED), college drinking intentions, and sociosexuality. Follow-up surveys at the end of the first and second college semesters assessed VSC and rape. Using the Sexual Experiences Survey’s severity scoring method, women were classified into one of three groups according to the most severe type of SV reported in the first year of college: neither VSC nor rape (71%), VSC (16%), and rape (13%). Most women who experienced rape (73%) also experienced VSC. Precollege SV and college drinking intentions predicted both rape and VSC. Sexual refusal assertiveness and high school HED did not independently predict either form of victimization. Sociosexuality predicted rape but not VSC. Findings suggest a substantial overlap in the predictors of VSC and rape and support the severity continuum underlying many conceptualizations of SV.